Dari Simbol Legendre ke Simbol Residu Kubik - Haryanto, Loeky; Afendi, Arman (Jurnal Matematika, Statistika dan Komputasi, 2018)
<img src="data:image/png;base64,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" alt="" width="456" height="149" />